The Impact of Stoicism Virtue Ethics on the Main Character’s Resilience Reflected in Stephen King’s Rita Hayworth and Shawshank’s Redemption - Atho, Muhammad Zainal; Thohiriyah, Thohiriyah (Syntax Literate, 2025)
This study investigates the perception of adversity and life uncertainty composed through the virtuous ethics of Stoicism in manifesting resilience embodied by Andy Dufresne, the protagonist in Stephen King’s Rita Hayworth and Shawshank Redemption (1982). Drawing on Waitzman’s (2024) framework of Stoic resilience, the analysis investigates how Andy navigates systemic oppression and adversity by grounding his actions in Stoic principles. The study aims to demonstrate how resilience emerges as the culmination of applied Stoic reasoning, wherein individuals reclaim agency through self-mastery and moral integrity. Methodologically, the study employs a close-reading analysis of the novel, supported by library research, to dissect Andy’s psychological and ethical strategies by integrating Stoic virtues: wisdom, courage, justice, and temperance. Additionally, with psychological constructs such as self-reliance, self-stability, and self-appropriateness, this article illuminates how resilience is actively forged through adversity rather than passive endurance. The findings demonstrate that Stoic resilience extends beyond basic survival as an intentional process guided by virtue, where adversity becomes a catalyst for autonomy and liberation. By combining literary analysis with moral philosophy and psychology, the interdisciplinary approach frames resilience as both a philosophical ideal and a practical tool for confronting life trials. This work contributes to broader discourses on resilience theory, advocating for future research to operationalize Stoic principles in real-world contexts, empowering individuals to harness adversity as a means of ethical and psychological growth.